2022
DOI: 10.1002/imt2.48
|View full text |Cite
|
Sign up to set email alerts
|

Tomato microbiome under long‐term organic and conventional farming

Abstract: The compartment niche is the main reason behind the shifts in endophytic bacterial communities. Long‐term organic greenhouse exerted limited influence on the variations of endophytic bacterial communities. Organic greenhouse and root had more complex co‐occurrence networks than conventional greenhouse and stem, respectively. Cultivable method results found that Protecbacteria, Bacteriodes, and Actinobacteria are the dominant phyla in the endophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Additionally, nitrate reductase ( NarG ) was in class 0 and can be represented by landmark genes that encode superoxide dismutase ( SOD ) and 4‐hydroxy‐tetrahydrodipicolinate synthase ( DapA ), both of which were critical enzymes in antioxidant systems, mainly involved in superoxide scavenging. This was also supported by the domain role of SOD in determining the microbial network in a previous study [35].…”
Section: Resultssupporting
confidence: 79%
“…Additionally, nitrate reductase ( NarG ) was in class 0 and can be represented by landmark genes that encode superoxide dismutase ( SOD ) and 4‐hydroxy‐tetrahydrodipicolinate synthase ( DapA ), both of which were critical enzymes in antioxidant systems, mainly involved in superoxide scavenging. This was also supported by the domain role of SOD in determining the microbial network in a previous study [35].…”
Section: Resultssupporting
confidence: 79%
“…Our data revealed that tomato core microbiota was dominated by phyla Proteobacteria, Actinobacteria, and Firmicutes in the substrate, rhizosphere, and fruit samples; comparable bacterial diversity has been reported in numerous studies with tomato plants cultivated in soil-based and SCSs [20,27,[63][64][65][66][67][68][69][70]. Together, these findings suggest that, regardless of the cultivation system, tomato plants have evolved a close biological interaction with members of Proteobacteria, Actinobacteria, and Firmicutes.…”
Section: Tomato Core Microbiota In Soilless Culture Systemssupporting
confidence: 85%
“…Particularly, it was revealed that most of the effects in the organic production system could be linked to Flavobacteriaceae , Erythrobacteraceae , Bradyrhizobiaceae , and Nocardioidaceae in substrates; Caulobacteraceae , Chitinophagaceae , Flavobacteriaceae, Rhodobacteraceae , Streptomycetaceae , in the rhizosphere; and Enterobacteriaceae in tomato fruit samples. These potential microbial biomarkers have been highlighted by other studies with tomato and lettuce cultivars [ 19 , 67 , 69 , 96 , 99 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, the relationship of metabolites associated with the microbial community assembly is difficult to identify. The joint application of the topological overlap matrix (TOM) algorithm of weighted correlation network analysis (WGCNA) and the important prediction of variables in the random forest model, identifying the “key” metabolites induce rhizosphere microbiome assembly and reflect the microbial community characteristics (keystone, dominant species, and Bray–Curtis distance) in the “rebuild” state [ 21 ]. In addition, root exudates directly impact the soil, further influencing the interactions with microorganisms.…”
Section: Introductionmentioning
confidence: 99%